Development and Perspectives of Landscape Ecology - Bastian, Olaf; Steinhardt, Uta (Springer Netherlands, 2002)
Development and status of landscape ecology - subject of this book During the last decades, landscape ecology has developed tremendously. It concerns both the theoretical basis and practical application. The roots of landscape ecology are geography and biology. The term "landscape ecology" was first coined by the German scientist Carl Troll in 1939. ünce, the devel opment center of landscape ecology was in Central Europe. Recently, also other parts of the world became powernd centers of landscape ecology, es pecially Northern America. American approaches partly differ essentially from the European, because they are focused esp. on biogeography and population dynamics. In Europe, however, the geographical roots of land scape ecology playamajor role. Landscape is defined as a complex of abiotic, biotic and human components. Mainly due to linguistic barriers, the international discussion does not take notice of approaches and experiences from non-anglophone countries in a sufficient manner. Therefore this book considers more the German and European views on landscape ecology than the books which were published before. It tries to bridge the gaps between theory and practice of landscape ecology, as well between the Ger manlEuropean and American approach es. The book gives a fundamental representation of landscape ecology, which proves to be a young, but an interesting and very important transdisci plinary science for the solution of environmental problems. Both the theo retical basis and practical application of landscape ecology are considered